1980
DOI: 10.1901/jaba.1980.13-629
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of Naming Responses to Objects in the Natural Environment as a Function of Training Stimulus Modality With Retarded Children

Abstract: Picture-cards, photographs, and real objects were compared as training stimuli in order to determine which best facilitated the generalization of naming responses learned in a special training room to real objects in the natural environments of four retarded children. The amount of transfer of naming behavior between the three stimulus modes and the average amount of training time required per stimulus mode were also assessed. Three of the four children displayed considerably more generalization to the real ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Two recent studies on sign language have yielded somewhat mixed findings regarding the effects of iconicity on acquisition. Griffith and Robinson (1980) found that subjects acquired iconic sign-word pairs more rapidly than non-iconic pairs, while Kohl (1981) (Welch & Pear, 1980 The purpose of the present study was to conduct several comparative analyses within a nonvocal language training program. Three cerebral palsied adolescents received concurrent instruction in the use of both Blissymbolics and a pictorial language, and their acquisition rates were compared.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Two recent studies on sign language have yielded somewhat mixed findings regarding the effects of iconicity on acquisition. Griffith and Robinson (1980) found that subjects acquired iconic sign-word pairs more rapidly than non-iconic pairs, while Kohl (1981) (Welch & Pear, 1980 The purpose of the present study was to conduct several comparative analyses within a nonvocal language training program. Three cerebral palsied adolescents received concurrent instruction in the use of both Blissymbolics and a pictorial language, and their acquisition rates were compared.…”
mentioning
confidence: 97%
“…On the one hand, it has been argued that Bliss symbols might facilitate better transfer than pictorial stimuli since, in the Bliss system, "conceptualization of a thought or idea is not tied to a specific picture" (Harris- , 1975). On the other hand, results of a study comparing pictorial representations versus real objects in teaching object naming have suggested that formal similarity enhances generalization (Welch & Pear, 1980). Unfortunately, these studies provide not only conflict-6 SHIRT F FOOT N WATCH 243 i ing, but also indirect evidence regarding differential outcome with Bliss versus iconic stimulus formats, since none of the research to date has incorporated an experimental comparison of the two procedures.…”
mentioning
confidence: 99%
“…Natural vs. artificial materials There is considerable empirical information about the generalizability of tasks taught with natural (i.e., real, three-dimensional materials) vs. artificial materials. Welch and Pear (1980) studied severely handicapped children who were taught to receptively identify objects in the training environment using either threedimensional objects, Peabody pictures, or photographs. They found that the children trained with real objects more readily generalized to novel real objects in natural environments, and that training in multiple environments further facilitated this generalization.…”
Section: Natural Vs Artificial Environmentsmentioning
confidence: 99%
“…Support for the learning effects of stimulus variation is well documented in the research literature. Systematically varying relevant and irrelevant stimulus conditions has been shown to be an important factor in facilitat ing generalized responding by learners with severe handicaps across novel objects, tasks, trainers, and set tings (e.g., Anderson & Spradlin, 1980;Handleman & Harris, 1980;Horner & McDonald, 1982;Welch & Pear, 1980). The present study investigated the effects of the ICS model in a preschool classroom for children with se vere disabilities.…”
mentioning
confidence: 98%